Effect of Fertility on Female Labour Force Participation in the United Kingdom. (May 2015) - Ukil, Patralekha
This article aims to estimate the causal effect of fertility on the labour force participation of British women. In order to account for the possible endogeneity of fertility variables, the sex composition of the two previous children of a mother has been used as an instrument for fertility. The Two-stage Residual Inclusion (2SRI) estimation method is used on a relatively new British data set—'Understanding Society'. The results suggest that fertility is indeed endogenous to the labour force participation decisions of women in the sample, and that not accounting for the endogeneity of the fertility variable leads to an exaggeration of the negative effect of fertility on female labour force participation. Important policy recommendations are drawn from the results. JEL Classification: J13, J22